A novel Mn/Co dual nanoparticle decorated hierarchical carbon structure derived from a biopolymer hydrogel as a highly efficient electro-catalyst for the oxygen reduction reaction. Issue 92 (1st November 2019) - Cao, Lujie; Wang, Zhenyu; Liu, Jinlong; Wang, Bingxue; Wang, Zhiqiang; Yang, Mingyang; Pan, Hui; Lu, Zhouguang
Abstract : A Mn/Co dual nanoparticle-decorated hierarchical carbon structure was derived from a Zn/Mn/Co/chitosan composite hydrogel as a highly efficient electro-catalyst for the oxygen reduction reaction. Abstract : A Mn/Co dual nanoparticle-decorated hierarchical carbon structure was derived from a Zn/Mn/Co/chitosan composite hydrogel. This strategy critically relied on the formation of a supramolecularly crosslinked hydrogel that allowed the efficient and homogeneous incorporation of highly active Mn/Co species onto the surface of hierarchical carbon structures. The resultant electrocatalyst outperformed Pt/C toward the oxygen reduction reaction in 0.1 M KOH electrolytes.